PELATIHAN BAGI GURU SMP YAPIS MERAUKE: PEMBELAJARAN OUTDOOR LEARNING DENGAN MATHCITYMAP - Dessy Rizki Suryani; Abdul Rachman Taufik (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Outdoor learning serves as a strategy to improve students' grasp of concepts and sharpen their practical abilities. However, its implementation at SMP YAPIS Merauke remains relatively low. Teachers still tend to rely on procedural approaches in classroom instruction due to limited pedagogical and technical competencies in utilizing outdoor environments as learning resources. Through this community engagement program, teachers were expected to develop both pedagogical and technical competencies in designing outdoor learning activities supported by MathCityMap. The program, conducted at SMP YAPIS Merauke, involved 22 teachers. Implementation methods included material presentation, guided practice, and evaluation. Evaluation was conducted using a teacher response questionnaire based on a Likert scale to measure participants’ understanding, the execution of activities, and the perceived benefits of the training. The results indicated that teacher responses were categorized as “Very Good,” suggesting that participants understood the concepts of outdoor learning and the use of MathCityMap, and found the training relevant and beneficial for their instructional practice. This program has positive implications for enhancing teacher readiness to design environment-based and contextual learning. Therefore, outdoor learning supported by MathCityMap has the potential to serve as an innovative alternative for improving the quality of mathematics instruction at the junior secondary level, particularly at SMP YAPIS Merauke.